(untitled) (Ascendens Asia Singapore – Union Christian College Philippines Journal of Multidisciplinary Research Abstracts, 2021)
The Covid-19 pandemic has transformed the lives of nurses who have provided exceptional care to Covid-19 patients despite the limited and inadequate resources of the healthcare system. When called to the forefront, nurses face insurmountable challenges and unimaginable experiences toward the healthcare system in general and the patients. Their efforts are commendable, and their contributions are worthy of recognition; hence, the people must learn to value and understand their role in the healthcare system. This study explores the experiences of nurses as front-liners during the Covid-19 outbreak. This study utilizes the interpretive method of phenomenology as a research design. The Ethics Review Board examined and approved the study before data gathering. Ethical Considerations are strictly followed in conducting qualitative data. Purposive sampling was used in the selection of participants. Unstructured interviews and zoom meetings were employed to collect the data. The Van Manen method of interpretation was used in analyzing the data gathered. Three themes unfolded from the study: These themes are, (1) Once in Constantinople (the challenges and fears they have experienced) with four related sub-themes, (2) the lamp (their coping mechanism, motivations, inspirations, desires in doing their job as a front-liners, including their organizational responsiveness and collegiality) with four related themes, and (3) the valiant-white patriot (their realizations as staff nurse during Covid-19 pandemic). This study will help the healthcare system, especially the hospitals, improve and enhance their policies and services concerning a pandemic response.